Quantification of host-mediated parasite clearance during blood-stage Plasmodium infection and anti-malarial drug treatment in mice. Issue 12 (October 2018) - Aogo, Rosemary A.; Khoury, David S.; Cromer, Deborah; Elliott, Trish; Akter, Jasmin; Fogg, Lily G.; Nair, Arya Sheela; Liligeto, Urijah N.; Soon, Megan S.F.; Thomas, Bryce S.; Pernold, Clara P.S.; Romanczuk, Aleksandra S.; et al.
Graphical abstract: Highlights: Parasitised-red blood cells (pRBCs) were removed with a half-life of 15 hours. Phagocyte-depletion approximately halved the rate of pRBCs removal. Mefloquine or artesunate (standard doses) did not alter pRBC removal rates. High-dose sodium artesunate doubled the rate of pRBC removal. Drugs primarily inhibit parasites, while phagocytes remove drug-affected pRBCs. Abstract: A major mechanism of host-mediated control of blood-stage Plasmodium infection is thought to be removal of parasitized red blood cells (pRBCs) from circulation by the spleen or phagocytic system. The rate of parasite removal is thought to be further increased by anti-malarial drug treatment, contributing to the effectiveness of drug therapy. It is difficult to directly compare pRBC removal rates in the presence and absence of treatment, since in the absence of treatment the removal rate of parasites is obscured by the extent of ongoing parasite proliferation. Here, we transfused a single generation of fluorescently-labelled Plasmodium berghei pRBCs into mice, and monitored both their disappearance from circulation, and their replication to produce the next generation of pRBCs. In conjunction with a new mathematical model, we directly estimated host removal of pRBCs during ongoing infection, and after drug treatment. In untreated mice, pRBCs were removed from circulation with a half-life of 15.1 h. Treatment with various doses of mefloquine/artesunate did not alter the pRBC removal rate, despite blocking parasite replication effectively. An exception was high dose artesunate, which doubled the rate of pRBC removal (half-life of 9.1 h). Phagocyte depletion using clodronate liposomes approximately halved the pRBC removal rate during untreated infection, indicating a role for phagocytes in clearance. We next assessed the importance of pRBC clearance for the decrease in the parasite multiplication rate after high dose artesunate treatment. High dose artesunate decreased parasite replication ∼46-fold compared with saline controls, with inhibition of replication contributing 23-fold of this, and increased pRBC clearance contributing only a further 2.0-fold. Thus, in our in vivo systems, drugs acted primarily by inhibiting parasite replication, with drug-induced increases in pRBC clearance making only minor contributions to overall drug effect.